Interactions of Intestinal Bacteria with Components of the Intestinal Mucus - Sicard, Jean-Félix; Le Bihan, Guillaume; Vogeleer, Philippe; Jacques, Mario; Harel, Josée (Frontiers in Cellular and Infection Microbiology, 2017)
The human gut is colonized by a variety of large amounts of microbes that are collectively called intestinal microbiota. Most of these microbial residents will grow within the mucus layer that overlies the gut epithelium and will act as the first line of defense against both commensal and invading microbes. This mucus is essentially formed by mucins, a family of highly glycosylated protein that are secreted by specialize cells in the gut. In this Review, we examine how commensal members of the microbiota and pathogenic bacteria use mucus to their advantage to promote their growth, develop biofilms and colonize the intestine. We also discuss how mucus-derived components act as nutrient and chemical cues for adaptation and pathogenesis of bacteria and how bacteria can influence the composition of the mucus layer.